2011
DOI: 10.1192/bjp.bp.110.090423
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of orthostatic blood pressure to white matter hyperintensities and subcortical volumes in late-life depression

Abstract: We found evidence for an association between the degree of orthostatic systolic blood pressure drop and WMH volume in the depression group. Since blood pressure drops lead to WMH in animals our findings suggest systolic blood pressure drops may be a factor contributing to these lesions in late-life depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
40
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 57 publications
4
40
0
1
Order By: Relevance
“…Depression is more frequent in patients with PD than in the non-PD population [30,31]. It has been suggested that cerebrovascular disease plays an important role in late-life depression [9]. However, we did not find any associations between the presence of CMBs and a history of depression in our patients.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…Depression is more frequent in patients with PD than in the non-PD population [30,31]. It has been suggested that cerebrovascular disease plays an important role in late-life depression [9]. However, we did not find any associations between the presence of CMBs and a history of depression in our patients.…”
Section: Discussionmentioning
confidence: 58%
“…This association has not been previously reported. Earlier studies have examined the associations between OH and other markers of cerebral small vessel disease, such as WMH, in patients with PD [8,20] and other populations [9,21], but the results have been inconsistent. The pathological substrates of WMH are heterogeneous in their nature and severity, which may partially explain the weak associations between the clinical factors and the radiological findings [22].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Several cases have reported that structural abnormalities in the brain may induce OI because specific brain regions modulate the cardiovascular autonomic nervous system (ANS) [4,5]. Moreover, previous studies have demonstrated a volume reduction of the brain in patients with OI [6,7,8]. However, no studies have investigated the cortical morphology of the brain in patients with OI.…”
Section: Introductionmentioning
confidence: 98%
“…Some evidence suggests that brain abnormalities are associated with OI [4,5,6,7,8]. Several cases have reported that structural abnormalities in the brain may induce OI because specific brain regions modulate the cardiovascular autonomic nervous system (ANS) [4,5].…”
Section: Introductionmentioning
confidence: 99%